The Influence of the Gini Ratio and the Human Development Index on the Poverty Severity Index in Deli Serdang Regency during the 2010–2025 Period. - Silvia Annur Hasibuan HASIBUAN; Monika Flora Manik; Rejosu Vanhot Sianturi (Outline Publisher, 2026)
This study aims to empirically analyze the effect of the Gini Ratio and the Human Development Index (HDI) on the Poverty Severity Index in Deli Serdang Regency during the 2010–2025 period. The study employs a quantitative approach, using multiple linear regression analysis to examine the relationship and magnitude of the influence between the independent variables and the dependent variable. The data used in this study are secondary time series data obtained from the Central Bureau of Statistics (BPS). The results indicate that the Gini Ratio has a positive and significant effect on the Poverty Severity Index, suggesting that increasing income inequality tends to exacerbate the severity of poverty. In contrast, the Human Development Index has a negative and significant effect, indicating that improvements in human development quality through education, health, and standard of living can reduce the severity of poverty. Simultaneously, both variables are proven to have a significant effect, with the model demonstrating a relatively strong explanatory power in explaining variations in the Poverty Severity Index. These findings confirm that poverty is a multidimensional phenomenon influenced not only by economic factors but also by the quality of human development and income distribution.